Multidimensional analysis of urban growth and informal consolidation in the Santa Rosa de Lima settlement, Peruvian Andes, Huancayo, Peru (1985–2025) - Arévalo Torres, Janis D’anna (2025)
The general objective of this study is to examine the socio - spatial development trajectory of the informal settlement Santa Rosa de Lima de Huancayo, Peru, over 40 years (1985 - 2025), focusing on unregulated urban development and infrastructure interventions. Adopting a longitudinal case study design with documentary analysis, systematic observation, and household interviews, this study explores four axes of development: social, economic, environmental, and urban - architectural. The analysis reveals extensive and largely unregulated urban expansion, marked by degradation of public open space, an increase in self - constructed residences, and a semi - structured urban landscape. This irregular pattern gradually develops partially structured streets and block configurations. A defining moment occurred with the 2011 opening of the Amazonas Bridge, enhancing connectivity and facilitating local government - led urban densification. Nonetheless, such infrastructure did not fully address ongoing issues such as environmental deterioration, vulnerable land tenure, and limited access to basic services. Its society confronts systemic inequities that have called for large - scale adaptability and resilience. Adaptive resilience in such cases is therefore the measures that residents implement to respond to problems, redesign their space, and incrementally improve their accommodations and common space, while fostering social cohesion. The research contributes to the scarce literature on long - term informal urbanization in mid - sized Andean cities that tend to be neglected in favor of megapolises. While the vast majority of Latin American research resorts to municipal archives, aerial photography, and surveying households, it takes up for the first time a four - decade - longitudinal multi - dimensional approach that sheds light on consolidation processes outside metropolitan areas. Results highlight the significance of the policy on allocative equity of land, participative plans approach, and sustainable services provision, in particular for the socio - environmental context characteristic of mountainous territories. Generalizability is restricted by the fact that data is collected at one point. It is recommended to undertake additional research in order to examine the multi - scalar governance structure, climate vulnerability, and longitudinal assessment to better understand the variables responsible for driving consolidation and resilience in similar informal settlements.